Documenting the prevalence of hiatal hernia and oesophageal abnormalities in brachycephalic dogs using fluoroscopy. (30th September 2017) - Reeve, E. J.; Sutton, D.; Friend, E. J.; Warren‐Smith, C. M. R.
Abstract : Objectives: To report the prevalence of abnormal fluoroscopic findings in brachycephalic dogs that were presented to a referral hospital for obstructive airway syndrome. Methods: Hospital records between May 2013 and November 2015 identified 36 brachycephalic dogs investigated for obstructive airway disease: 21 French bulldogs, six bulldogs, four Boston terriers, two pugs, two boxers and one shih‐tzu. The presence or absence of hiatal hernia, delayed oesophageal transit, gastro‐oesophageal reflux and redundant oesophagus were recorded. Results: Of the 36 dogs, 16 had hiatal hernia, all of which were French bulldogs; 31 dogs had delayed oesophageal transit time, 27 had gastro‐oesophageal reflux, and four had redundant oesophagus. Clinical Significance: Clinical Significance: The prevalence of hiatal hernia is higher than expected in the French bulldog, and there was a high prevalence of oesophageal disease in this group in general. These results suggest a need to investigate similar cases for evidence of gastrointestinal disease that may also require attention.